The Effect of Tax Sanctions on The Level of Taxpayer Compliance at The Tax Service Office Pratama Madya Medan - Sari Raphyta Olivia Grace (Britain International for Academic Research (BIAR) Publisher, 2022)
This study aims to determine whether there is an effect of taxpayer awareness and tax sanctions on taxpayer compliance at KPP Pratama Madya Medan. The population in this research are taxpayers who are registered at KPP Madya Medan. Data analysis using multiple linear regression. The results of the study show that taxpayer awareness and tax sanctions have an effect on taxpayer compliance